Comparative Analysis of some Water Quality Parameters of three Lakes in Jahangirnagar University Campus, Savar, Bangladesh (Bangladesh Journal of Zoology, 2016)
Study was conducted to determine the physico-chemical parameters of water of three different lakes in Jahangirnagar University campus from March to November, 2013. The selected parameters were water depth, water temperature, conductivity, transparency, pH, dissolve O2, free CO2, total alkalinity, hardness, sulfate and water color. Water depth fluctuated from 140 cm to 385 cm, temperature ranged from 250C to 310C, conductivities ranged from 627 ?S/cm to 1544 ?S/cm, transparency from 22 cm to 87 cm, considerable variation of water colors were found and pH ranged from 6.4 to 7.5 without having any significant fluctuation. Dissolve oxygen (DO) ranged from 2.7 mg/l to 7.6 mg/l, carbon dioxide level ranged from 16 mg/l to 62 mg/l, total alkalinity and hardness were ranged from 43 mg/l to 92 mg/l and 63 mg/l to 134 mg/l, respectively with slight variations in different lakes in different months. During the study period, all the spots showed minimum fluctuation of physico-chemical parameters from the normal range without having some exceptions.Bangladesh J. Zool. 43(2): 239-250, 2015